Tata Kelola Kelautan, Governansi Ekonomi, dan Investasi Berkelanjutan di Asia Tenggara - Pujawanti Saragih (CV. ITTC INDONESIA, 2026)
This research examines the interrelationships between marine governance, economic governance, and sustainable investment, focusing on Southeast Asian and Indo-Pacific case studies. Using a qualitative approach based on policy studies and recent empirical studies, this research explores how blue economy policies are implemented in Indonesia, the Philippines, and Timor-Leste. The analysis shows that integrated marine governance can strengthen maritime economic stability, increase investment transparency, and support the achievement of Sustainable Development Goals (SDG 14). The implementation of Marine Spatial Planning in Indonesia and cross-border blue economy projects in ASEAN demonstrate positive synergies between the public and private sectors. This research confirms that adaptive and participatory marine governance is key to the success of sustainable marine economic development in the Asia-Pacific region.